Media Pembelajaran Islam Mengenal Mahram Berbasis Animasi Menggunakan Adobe Flash - Risa Fauziah Nur; Nenna Irsa Syahputri; Dharmawati (LKP Unity Academy, 2023)
The mahram used by the people is taken from Arabic. Mahram is a woman or a man who is still a close relative so it is not permissible to marry between the two. Mahram relationships can occur for three reasons, namely heredity, breastfeeding, and marital relations. Mahram can be sourced from the verses of the Qur'an and Al-Hadith. However, nowadays there are still many people who do not know which is mahram or not. The purpose of this study is to build an application system that will be a medium for users, especially Muslims to know the mahram and make it easier for us to know the mahram of the family. This application is designed using Adobe Flash CS6 which has a pretty good performance. The system development method used is the literature study method, which collects supporting data related to research such as from social media, websites or other sources. Based on the test results, the genealogy application is running successfully on the Windows 10 operating system. This research produces an application with the main function as a medium that requires information about mahram in Islam and provides the desired convenience and speed.